2023
DOI: 10.3389/fncel.2022.1036313
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy regulates inflammation in intracerebral hemorrhage: Enemy or friend?

Abstract: Intracerebral hemorrhage (ICH) is the second-largest stroke subtype and has a high mortality and disability rate. Secondary brain injury (SBI) is delayed after ICH. The main contributors to SBI are inflammation, oxidative stress, and excitotoxicity. Harmful substances from blood and hemolysis, such as hemoglobin, thrombin, and iron, induce SBI. When cells suffer stress, a critical protective mechanism called “autophagy” help to maintain the homeostasis of damaged cells, remove harmful substances or damaged org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 162 publications
(190 reference statements)
0
4
0
Order By: Relevance
“…Therefore, we speculate that after Trem2 knockout, the degradation efficiency of microglia is improved. Further, studies have found that in a two‐point injection of the LPC demyelination model, the overactivation of microglial autophagy lysosomes can lead to the accumulation of lipid droplets, causing microglial dysfunction and transformation to a pro‐inflammatory phenotype (Fu et al., 2022; Zhou et al., 2023). In the aging brain, lipid droplets accumulated in microglia can also cause microglial dysfunction and strong inflammatory responses (Qin et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we speculate that after Trem2 knockout, the degradation efficiency of microglia is improved. Further, studies have found that in a two‐point injection of the LPC demyelination model, the overactivation of microglial autophagy lysosomes can lead to the accumulation of lipid droplets, causing microglial dysfunction and transformation to a pro‐inflammatory phenotype (Fu et al., 2022; Zhou et al., 2023). In the aging brain, lipid droplets accumulated in microglia can also cause microglial dysfunction and strong inflammatory responses (Qin et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy plays a vital role in degrading intracellular materials and maintaining cellular homeostasis by utilising lysosomal enzymes [ 48 ]. The production and transportation of autophagosomes primarily occur in axons, and proper axonal transport is crucial for clearing damaged mitochondria [ 19 ]. Ctsb is closely associated with autophagy and negatively regulates neurite outgrowth by modulating lysosomal trafficking in neurons [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Following a stroke, various forms of cell death occur in the body, the main ones of which are apoptosis ( 139 ), necrosis ( 140 ) and autophagy ( 141 ). It has been shown that the use of different inhibitors to inhibit apoptosis, necrosis and autophagy is more effective than the use of any of these inhibitors in isolation, as in the case of cerebral hemorrhage, where caspase inhibitors have been shown to be unsuccessful in terms of inhibiting hemoglobin-induced neuronal death ( 142 ).…”
Section: Ferroptosis Inhibitors and Strokementioning
confidence: 99%